2003
DOI: 10.1016/s0012-1606(03)00222-7
|View full text |Cite
|
Sign up to set email alerts
|

A role for programmed cell death during early neurogenesis in xenopus

Abstract: In vertebrates, little is known on the role of programmed cell death (PCD) occurring within the population of dividing neural precursors and newly formed neuroblasts during early neural development. During primary neurogenesis, PCD takes place within the neuroectoderm of Xenopus embryos in a reproducible stereotypic pattern, suggesting a role for PCD during the early development of the CNS. We find that the spatio-temporal pattern of PCD is unaffected in embryos in which cell proliferation has been blocked and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 44 publications
11
63
1
Order By: Relevance
“…The presence of significant levels of apoptosis in the proliferative zone of the mouse brain (Blaschke et al 1996), since then confirmed in other species including the human (Rakic and Zecevic 2000;Yeo and Gautier 2003), suggested that cell death is not a phenomenon exclusively restricted to postmitotic neurons, but this did not necessarily imply that apoptosis regulation was linked to brain patterning. A first important hint came from the analysis of caspase gene invalidation in mutant mice: The mutants invalidated for pro-apoptotic genes Caspase-3, Caspase-9, and Apaf1 present a similar phenotype, consisting in a drastic reduction in early cerebral apoptosis and an inappropriate amplification of specific populations of neural progenitors, resulting in brain exencephaly and neural overgrowth (Cecconi et al 1998;Hakem et al 1998;Kuida et al 1996;Kuida et al 1998;Pompeiano et al 2000).…”
Section: Early Neural Cell Death and Brain Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of significant levels of apoptosis in the proliferative zone of the mouse brain (Blaschke et al 1996), since then confirmed in other species including the human (Rakic and Zecevic 2000;Yeo and Gautier 2003), suggested that cell death is not a phenomenon exclusively restricted to postmitotic neurons, but this did not necessarily imply that apoptosis regulation was linked to brain patterning. A first important hint came from the analysis of caspase gene invalidation in mutant mice: The mutants invalidated for pro-apoptotic genes Caspase-3, Caspase-9, and Apaf1 present a similar phenotype, consisting in a drastic reduction in early cerebral apoptosis and an inappropriate amplification of specific populations of neural progenitors, resulting in brain exencephaly and neural overgrowth (Cecconi et al 1998;Hakem et al 1998;Kuida et al 1996;Kuida et al 1998;Pompeiano et al 2000).…”
Section: Early Neural Cell Death and Brain Morphogenesismentioning
confidence: 99%
“…In vertebrates, the contribution of apoptotic processes to neural regional patterning remains unclear at this stage, although the patterns of neural progenitor apoptosis are strikingly dynamic in time and space (Blaschke et al 1996;Rakic and Zecevic 2000;Yeo and Gautier 2003). On the other hand, several extracellular cues have been recently identified that control early neural cell death.…”
Section: Early Neural Cell Death and Brain Morphogenesismentioning
confidence: 99%
“…Under normal conditions, TUNEL staining is low or absent during gastrulation and neurulation, probably due to the rapid degradation of apoptotic cells with a turnover time of 1 h or less (Jacobson et al 1997;Hensey and Gautier 1998;Yeo and Gautier 2003). Cell cycle inhibition slows down the rate at which dying cells are degraded, thus allowing more cells to be detected by TUNEL at a given time (Yeo and Gautier 2003).…”
Section: Id3 Is An Essential Early Regulator Of Neural Crest Formationmentioning
confidence: 99%
“…Cell cycle inhibition slows down the rate at which dying cells are degraded, thus allowing more cells to be detected by TUNEL at a given time (Yeo and Gautier 2003). Id3-depleted embryos clearly showed increased TUNELpositive staining on the injected side, possibly due to a blockade of the cell cycle and subsequent cell death.…”
Section: Id3 Is An Essential Early Regulator Of Neural Crest Formationmentioning
confidence: 99%
“…This phenomenon involved the expression of several developmental genes such as Xotx2 or Xrx1 [48]. In X. laevis, Yeo and Gautier showed that PCD regulated the primary neural determination [49]. A third wave of apoptosis was then observed on late neurulation, when axons develop from maturating neurones.…”
Section: Discussionmentioning
confidence: 99%